Improved outcomes of scar revision with the use of polydioxanone suture in comparison to polyglactin 910: A randomized controlled trial. Issue 8 (August 2018) - Gupta, Deepti; Sharma, Upendra; Chauhan, Shashank; Sahu, Shamendra Anand
Summary: Scars have multiple cosmetic and functional sequelae, and revision surgeries are an attempt to ameliorate these effects. Reduction of spread of the revised scar is one of the main objectives of revision procedures. Provision of prolonged dermal support to wound can theoretically reduce spread of the scar. We carried out a randomized controlled trial and objectively evaluated the impact of two commonly used absorbable sutures, Polyglactin 910 and Polydioxanone, on scar spread and quality. Sixty patients with post-traumatic scars of 1 year in duration were enrolled in the study and randomly divided into two groups of 30 each. After recording the demographic data and baseline scar characteristics, revision of the scar was carried out by elliptical excision and primary suturing. In Group 1, Polyglactin 910 6-0 suture (Vicryl, Ethicon, Johnson and Johnson Ltd., India) was used for dermal suturing, whereas, in Group 2, Polydioxanone 6-0 suture (PDS II, Ethicon, Johnson and Johnson Ltd., India) was used. The scar spread in terms of scar width, and scar quality with Vancouver Scar Scale (VSS) was evaluated at 1, 3 and 4 months postoperatively. The two groups were well matched for demographics and baseline scar characteristics. On follow-up, the mean scar width in Group 1 was significantly more than that in Group 2. VSS score was significantly lower in Group 2 at the third and fourth month follow up, signifying better scar quality. Suture extrusion was noticed in 3 cases in Group 1. Compared to Polyglactin 910, Polydioxanone sutures, when used for intradermal suturing in revision of facial scars, result in a significantly decreased scar spread and better scar quality.